Origins of neurosurgery in the beginning of the XIXth century in Vilnius clinics - Sakalauskaitė-Juodeikienė, Eglė; Kvaščevičius, Robertas; Jatužis, Dalius (Lietuvos chirurgija, 2018)
[full article and abstract in Lithuanian; abstract in English]ObjectivesBefore the end of the XIXth century neurosurgical operations were rarely performed in European university clinics and city hospitals. The development of neurosurgery was not possible without major medical discoveries: anaesthetics and antiseptics, effective haemostasis and atraumatic surgical techniques. The aim of this work is to discover the origins of neurosurgery, to determine what type of surgical operations of the nervous system were performed in the beginning of the XIXth century in Vilnius.Material and methodsWe analyzed doctoral theses devoted for neurosurgery and defended in Imperial university of Vilnius during 1803–1832.ResultsFive theses (out of 26) were included into analysis: dissertation on brain commotion, external head injuries, trepanation, encephalocele and brain fungus, and the ligation of the common carotid artery. Evaluating patients with external head injuries, University professors and students performed primitive neurological examination and estimated signs of brain compression.Dizziness, somnolence and stupor, stertorous breathing, headache and weakness of voluntary movements were evaluated, taking the side of hemiplegia as one of the most important signs. If the patient presented with head trauma which caused brain compression, but no external head injuries and signs of skull fractures were observed, then the side of limbs paralysis was evaluated and trepanation performed contralaterally to paralysis. Post mortem examinations of the deceased patients in Vilnius Surgery clinic were performed to confirm the clinical diagnosis.ConclusionsThe origin of neurosurgery in Vilnius goes back to the beginning of the 19th century. Trepanation, evacuation of epidural or subdural hematomas, ligation of the common carotid artery and excision or ligation of the surface head tumors were performed in Vilnius Surgery clinic.
Keywords: Imperial university of Vilnius, nineteenth century, neurosurgery, trepanation, cerebral localization